Effectiveness of Health Insurance Project; Women Satisfaction Regarding Quality of Ante-natal Services - Mohamed Gamal Elsehrawy, Fatma El Emam Hafeze Elemam, Heba Ali Hamed Mohamed, Mudathir Mohamedahmd Eltayeb, Elturabi Elsayed Ebrahim, Maha Moussa Mohamed Moussa, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aimed to evaluate the effectiveness of the universal health insurance project regarding the quality of health care with antenatal care services. Materials and methods: A descriptive comparative study carried out at ten Primary Health Care (PCH) centers affiliated to Port-said and Damietta governorates. Multi-stage sampling probability technique used for selecting these centers, simple random sample of 460 women chosen. Data was collected through two tools; women's satisfaction questionnaire, and Support Tool for Improving Quality of Antenatal Care. Results: the study results revealed that 69.1% of women were unsatisfied with the antenatal care services and available resources provided by the traditional insurance. On the other hand, 79.1% of women receiving universal health insurance were satisfied with the services provided. Conclusion: level of satisfaction was higher among women using universal health insurance regarding the recent health care services, cleanness, arrangement of medical facilities, availability of resources and criteria of service.